Davide Ferrario's architecture of cinema: Body, building, line. Issue 2 (1st March 2019) - Lerner, L. Scott
In Davide Ferrario's Dopo mezzanotte (After Midnight) (2004) the Mole Antonelliana serves to inspire a story, within which it endures as the central locus of the plot and setting. In Guardami ('Look at me') (1999a) a similar role is played by 'a body' (belonging to a porn star), while in La luna su Torino (45th Parallel) (2013), such a role is played by 'a line'. Ferrario's architecture of cinema thus consists of the adoption of a primary element and formal constraint (the body, the building, the line), which in turn are used as a means of generating a cinematic story. Whether integral to a comedy or to a drama, these stories, thus generated, do not remain sequestered in an isolated aesthetic, but engage powerfully with important questions of our times: What does a 'balanced' life look like? How does it feel to adopt a wholly secular view of the human body, to see and live within such a body?